Experiences with stigma and discrimination among adolescents and young adults living with HIV in Bangkok, Thailand. Issue 4 (2nd April 2020) - Mathew, Rhea S.; Boonsuk, Phiangjai; Dandu, Madhavi; Sohn, Annette H.
ABSTRACT: Thailand has identified stigma and discrimination as barriers to controlling their HIV epidemic. We aimed to explore the perspectives of young adults living with HIV in Bangkok regarding the influence of stigma and discrimination in education, employment, health care, personal relationships, and perceptions of self. Participants aged 15–24 years were conveniently and purposively sampled from local HIV clinics in Bangkok. Twenty-three individuals (14 female, 9 male; median age 20) were enrolled into the study between May and June 2017. Semi-structured qualitative interviews were conducted in Thai. Interview transcripts were translated into English and analyzed with Dedoose software (v7.6.12) using a framework analysis approach. Participants reported varied experiences with and beliefs about HIV-related stigma as they related to family, employment, education, and society. While few experienced discrimination, such as losing opportunities at work or school, all reported anticipating potential stigma and fearing negative repercussions from disclosure. Many participants reported that fear of disclosure negatively impacted their medication adherence. For the individuals interviewed, fear of stigma was a daily consideration. Many experienced HIV-related stigma in school, at work, within their communities, and in their inter-personal relationships. Anti-stigma efforts should include strategies that address the needs of young adults.